The time bomb within (Managing stress, 1984)
An introduction to managing stress, explaining why the stress response occurs and why its dangers are felt by so many people. Outlines major health consequences of unrelieved stress and suggests ways to lessen its effects. Suggested audience: senior secondary, tertiary, special groups.